2008
DOI: 10.1590/s1982-56762008000600004
|View full text |Cite
|
Sign up to set email alerts
|

Silicato de potássio na proteção do cafeeiro contra Cercospora coffeicola

Abstract: das principais doenças da cultura do café (Coffea arabica L.) desde o viveiro até o campo. As plantas doentes apresentam desfolha, redução no desenvolvimento e raquitismo, levando a uma diminuição na produção do cafeeiro (Chalfoun, 1997).O principal método de controle da cercosporiose é o químico, no entanto, o uso indiscriminado de fungicidas tem causado danos ao meio ambiente e aos seres vivos. Uma alternativa no manejo de doenças seria a utilização da indução de resistência (Bettiol, 1991). A resistência in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
6
0
2
Order By: Relevance
“…tritici in wheat (Belanger et al, 2003) and control of Erysiphe graminis in barley (Carver et al, 1987). Then, promising results in reducing disease intensity were found in various pathosystems, also in dicots, including Cercospora leaf spot and rust in coffee (Pozza et al, 2004;Botelho et al, 2005;Amaral et al, 2008;CarreMissio et al, 2014), pestalotiopsis leaf spot and powdery mildew in strawberry (Palmer et al, 2006;Kanto et al, 2006;Kanto et al, 2007;Carré-Missio et al, 2010), powdery mildew in melon, squash and cucumber Samuels et al, 1991), rust in soybean Lima et al, 2010), anthracnose in common-bean and sorghum (Moraes et al, 2009;Polanco et al, 2012;Resende et al, 2013) and root rot in tomato and avocado (Heine et al, 2007;Bekker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…tritici in wheat (Belanger et al, 2003) and control of Erysiphe graminis in barley (Carver et al, 1987). Then, promising results in reducing disease intensity were found in various pathosystems, also in dicots, including Cercospora leaf spot and rust in coffee (Pozza et al, 2004;Botelho et al, 2005;Amaral et al, 2008;CarreMissio et al, 2014), pestalotiopsis leaf spot and powdery mildew in strawberry (Palmer et al, 2006;Kanto et al, 2006;Kanto et al, 2007;Carré-Missio et al, 2010), powdery mildew in melon, squash and cucumber Samuels et al, 1991), rust in soybean Lima et al, 2010), anthracnose in common-bean and sorghum (Moraes et al, 2009;Polanco et al, 2012;Resende et al, 2013) and root rot in tomato and avocado (Heine et al, 2007;Bekker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This element is absorbed by the plant in the form of monosilicic acid (H 4 SiO 4 ) along with water (mass flow) and accumulates mainly in the maximum perspiration areas as polymerized silicic acid. It promotes the effective control of plant diseases (Amaral et al, 2008;Guével et al, 2007;Pozza et al, 2009) and has been associated with reduced effects of harmful chemical and physical agents (Zhu et al, 2004, Ma & Yamaji, 2006. The benefits of Si can be observed in the growth and production of many grasses such as rice, oats and maize (Wang et al, 2004, Hossain et al, 2007Zanão Júnior et al, 2009) and in some species that are not grass, such as tomatoes and lettuce (Lana et al 2003;Resende et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The species V. x wittrockiana showed 15% more protein when, considering the maximum species production ( Figure 1F). Amaral et al (2008) working with silicate in coffee, observed that plants sprayed with the product showed a significant increase in peroxidase activity (pathogenesisrelated protein) at five days after spraying when compared to the activity of this enzyme in control plants.…”
Section: Proteinmentioning
confidence: 99%
“…Many authors report that Si fertilization provides an 2005; Amaral et al, 2008), soybean (Moraes, 2009), potato (Gomes, 2005;Gomes et al, 2008), rice (Fleck et al, 2011;Suzuki et al, 2012) and orchid (Mantovani et al, 2018). On onion.…”
Section: Introductionmentioning
confidence: 99%